Isolation and Identification of Talaromyces sp. Strain Q2 and Its Biocontrol Mechanisms Involved in the Control of Fusarium Wilt - Tian, Yehan; Zhao, Yang; Fu, Xuesong; Yu, Chengming; Gao, Kexiang; Liu, Huixiang (Frontiers in Microbiology, 2021)
Fusarium wilt is an important disease of many food crops and often causes serious damages to yield and food quality. Consequently, numerous studies mainly focused on exploring the control strategy for Fusarium oxysporum as well as the mechanism of interaction between the F. oxysporum and other beneficial soil microorganisms. In this study, we have screened and identified an efficient biocontrol strain from the soil with infection of F. oxysporum f. sp. momordica (referred to as Fom), Talaromyces purpurogenus Q2 (referred to as TpQ2), which could be effective to reduce relative abundance of the rhizospheric Fom, leading to a significant decrease of Fusarium wilt disease incidence in bitter gourd during the greenhouse and field trails. The mechanism of TpQ2 can reduce the relative abundance of rhizospheric Fom through inhibition of growth and development of Fom. During the co-cultivation of TpQ2 and Fom, we confirmed that TpQ2 could significantly suppress the growth and development of Fom through disturbing the normal hyphae shape and function of the cell walls of Fom via secreting cell wall degrading enzymes and suppression of the expression of a cell wall biosynthesis genes, such as FomCFEM. In the meantime, TpQ2 showed a strong negative correlation with F. oxysporum in soil and positive correlation with beneficial indigenous microorganisms that had significant negative correlation with Fusarium populations, such as Streptomycetes, Lysobacter, and Sphingobium. To summarise, TpQ2 has a good biocontrol efficacy on Fusarium wilt of bitter gourd. The biocontrol mechanisms of TpQ2 on Fusarium wilt are complex and diverse.